ANALISIS PENTINGNYA PENGELOLAAN PERPUSTAKAAN DI LINGKUNGAN SEKOLAH SMA NEGERI 1 SAMBUNGMACAN - Lutfi Gesang Saputra, Alan; Mahdi, Mahdi (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2023)
The purpose of this study was to explore the Library of SMA Negeri 1 Sambungmacan based on the National Library Standard, IFLA/UNESCO School Library Guidelines and the description of the Library of SMK Negeri 2 Surakarta. This research is a type of qualitative survey conducted in the library of SMA Negeri 1 Sambungmacan. The sampling method used the Snowball sample with a case study approach. Interviews with librarians, staff and library visitors of SMA Negeri 1 Sambungmacan, observations or conditions of SMA Negeri 1 Sambungmacan, and documents related to this study were used for data collection. The conclusion of this study is that the Library of SMA Negeri 1 Sambungmacan has library management, buildings, collections of library materials, staff and services. Based on National Library standards, the building area of the SMA Negeri 1 Sambungmacan Library is not yet valid. The limitations of library management in SMA Negeri 1 Sambungmacan are that they have just started learning geography and SMA Negeri 1 Sambungmacan has not allocated priorities or budgets for classrooms used for teaching and learning activities.